Brief report: Can irritability act as a marker of psychopathology?. Issue 4 (31st March 2014) - Mulraney, Melissa; Melvin, Glenn; Tonge, Bruce
ABSTRACT: Irritability is ubiquitous in child and adolescent psychopathology. This study aimed to determine if the Affective Reactivity Index (ARI), a measure of irritability, could be used to screen for psychopathology in adolescents. The clinical sample comprised 31 adolescents with a DSM‐IV diagnosis. The control sample was 31 gender and age matched adolescents recruited through schools. Both samples completed a test battery that included the Affective Reactivity Index. The clinical participants reported significantly higher levels of irritability than the control sample by both self‐ and parent‐report. Using ROC analysis a cut off value of 4 on the self‐report ARI was found to be optimal for indicating psychopathology; with a specificity of 77.4% and a sensitivity of 77.4%, the area under the curve was 0.86. This paper provides evidence to suggest that irritability may be used as a general predictor of psychopathology in adolescents.